Energy Loss Due to Adhesion During the Impact of Elastic Spheres. (2017) - Jayadeep, U.B.; Bobji, M.S.
Abstract: The impact of elastic spheres in presence of adhesion has been extensively studied due to its wide-ranging significance. A major emphasis of such studies is the energy loss occurring during impacts. Energy loss due to elastic stress waves is of special significance, as it could be the only active energy loss mechanism in many cases. In this work, we use finite element method to study the impact of elastic spheres on a rigid half-space in presence of adhesion. Adhesion, caused by van der Waals force, is modeled as a body force. This formulation helps to avoid many of the restrictions imposed by the commonly-used surface-force model of adhesion. The energy loss in adhesive impact of elastic spheres is predominantly due to the stress waves caused by adhesion-induced instability, which is absent below a critical sphere radius. Therefore, the coefficient of restitution increases with increase in sphere radius below this critical value, while it shows a reducing trend above it, within the range of sphere radii considered in this study. Therefore, our study indicates that the variation of critical velocity for capture with sphere radius will not be monotonic, unlike presented in many of the previous studies.